Current trend of bacteriological sensitivity patterns from superficial and deep wounds in pressure ulcers - Lunawat, Ajay; Vashistha, Rishi Kant; Patidar, Himanshu; Patel, Vishad (International Surgery Journal, 2016)
Background:To investigate the incidence of different bacteria isolates in 50 samples of superficial pus culture and deep tissue specimen from pressure ulcer in a tertiary health care centre in central India and their antibacterial susceptibility patterns. Methods: Wound swab and tissue samples were collected from grade III/grade IV pressure ulcer and cultured for bacterial isolates. The isolates were characterized and identified by standard microbiological methods. Antibiotic susceptibility testing was carried out. Results:Out of 50 specimens of superficial pus culture, 98% were infected with bacteria. Predominant isolate was of staphylococcus aureus (42%), pseudomonas (28%), streptococcus (18%) and E. coli (14%). Deep tissue culture of same specimens showed that there was no growth in 17 (34%) specimen. Pseudomonas was isolated in 14 (28%) and Klebsiella in 9 (18%). Conclusions:We suggest a multidisciplinary approach to wound management, routine microbiological surveillance of wounds, rational drug use and the institution of strong infection control policies.